Study and comparison of next generation sequence algorithms and tools - Yates, Heath Landon (Kansas State University, 2014)
This study is a comparison and exploration of next generation sequencing algorithms and tools. A simulation study was done to compare the performance of edgeR, DESeq, and baySeq in detecting differential gene expression. The methods were compared in context of a balanced pairwise design. The simulation results suggest that the methods are compa- rable under the conditions simulated. The study also explored real data comprised of one biological replicate between two treatments. Cufflinks and CummerRBund were used to detect differential gene expression. The visualization results from the real data suggest no differential expression is present.
Keywords: NGS; BaySeq; EdgeR; DESeq; Cufflinks; Computer Science (0984)